2005
DOI: 10.1046/j.1540-8167.2005.40579.x
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Internal Defibrillation in Brugada Syndrome: Focus on Refractoriness and Ventricular Fibrillation Cycle Length

Abstract: Patients with Brugada syndrome have a high prevalence of high defibrillation energy requirement, and short ventricular ERP and VFCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
(36 reference statements)
1
20
0
1
Order By: Relevance
“…We found that 12% of the patients had a DFT Ͼ21 joules, whereas 4.6% 20 to 6.2% of patients with structural heart disease 21 are reported to have a high DFT. A previous study by Watanabe et al 19 found 18% of 22 Brugada patients with a DFT Ͼ25 joules versus 0% in the group implanted with ICDs for structural heart disease. Two hypotheses have been proposed to explain these findings.…”
Section: Icd Implantation Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…We found that 12% of the patients had a DFT Ͼ21 joules, whereas 4.6% 20 to 6.2% of patients with structural heart disease 21 are reported to have a high DFT. A previous study by Watanabe et al 19 found 18% of 22 Brugada patients with a DFT Ͼ25 joules versus 0% in the group implanted with ICDs for structural heart disease. Two hypotheses have been proposed to explain these findings.…”
Section: Icd Implantation Parametersmentioning
confidence: 93%
“…With regard to implantation data, it has been suggested that Brugada patients have high DFTs 19 and high pacing thresholds. We found that 12% of the patients had a DFT Ͼ21 joules, whereas 4.6% 20 to 6.2% of patients with structural heart disease 21 are reported to have a high DFT.…”
Section: Icd Implantation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It is mainly observed in patients with ICD dysfunction, 11 lead dislocation, 12 structural heart disease such as hypertrophic cardiomyopathy, 13,14 reduced ejection fraction, electrical storm, 15 metabolic decompensation, 16 and Brugada syndrome. 17 An initial report by Bardy et al 6 showed that the S-ICD successfully detected and treated all 12 episodes of spontaneous sustained ventricular tachycardia. However, these episodes occurred in only 3 patients, with 1 patient experiencing an electrical storm.…”
Section: Ineffective Shock Delivery In S-icd and Transvenous Icdsmentioning
confidence: 99%
“…The study of Watanabe et al [12] examined the incidence of VF not responding to internal defibrillation and found an incidence of 18%. One explanation could be the origin of the electrical abnormality at the level of RVOT [13] with defibrillation shock delivered between the right ventricular apex and left subclavicular can.…”
Section: Unsuccessful Internal Defibrillation In Brugada Syndromementioning
confidence: 99%